Simian virus 40 mutants carrying two temperature-sensitive mutations. - Chou, J Y (1976)
Five temperature-sensitive mutants of simian virus 40 containing two temperature-sensitive mutations were isolated. The double mutant of the A and D complementation groups, like the D mutants, failed to complement by conventional complementation analysis and did not induce host DNA synthesis at 40 degrees C. However, under conditions that suppressed the D defect, the A:D double mutant expressed only the A defect. Thus, viral DNA replication dropped rapidly after this mutant was shifted from permissive to restrictive temperatures. The A:D double mutant failed to transfrom at the restrictive temperature when subconfluent Chinese hamster lung monolayers were used. Double mutants of A:B, A:C, and A:BC complementation groups, like their A parent, were defective in viral DNA replication, in the induction of host DNA synthesis and in the transformation of secondary Chinese hamster lung cells at the nonpermissive temperature.